Drawing teaching: a look at courses of the department of arts of Federal University of Paraná (1981-1987) - Silva, Rossano (2019)
The present paper proposes to investigate drawing teaching in the courses offered by the Department of Arts (DEARTES) of Federal University of Paraná, including the courses of Industrial Designand the bachelor’s degrees in Artistic Education, Arts and Design qualifications. The research focus investigates the courses syllabus between 1981 and 1987, in which the drawing disciplines were taught by both DEARTES and the Design Department (DDES), which had different configurations of the drawing concept. This paper is organized into three parts: 1) Interlocutions between the Departments of Arts and Design; 2) Industrial Design, Visual Communication and Design and Plastic Arts syllabus; 3) Prescriptions of drawing teaching and Plastic Arts. To carry out the proposed analysis, the theoretical reference used is based on the concept of figuration by Elias, field by Bourdieu and the contributions on the history of school subjects by Chervel and Goodson. The sources used are official documents, discipline programs and minutes. This allowed the drawing prescriptions analysis that composed the syllabus of the above mentioned courses.